The female athlete triad, relative energy deficiency in sport, and the male athlete triad: The exploration of low-energy syndromes in athletes - Statuta, S. M. (Current Sports Medicine Reports, 2020)
The female athlete triad (FAT) is a three-pronged spectrum of interrelated medical conditions among physically active females (1,2). With emerging data, each specific component has morphed into its current definition: